Project recovery : case studies and techniques for overcoming project failure - Kerzner, Harold (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
Best practices for picking up the pieces when projects fail There are plenty of books available offering best practices that help you keep your projects on track, but offer guidance on what to do when the worst has already happened. Some studies show that more than half of all large-scale project fail either fail completely, or at least miss targeted budget and scheduling goals. These failures cost organizations time, money, and labor. Project Recovery offers wise guidance and real-world best practices for saving failed projects and recovering as much value as possible from the wreckage. Sinc.
4.3 Roles, Responsibilities and Decision-Making Authority4.4 Governance Frameworks; 4.5 Governance Failures; 4.6 Why Projects are Hard to Kill; 4.7 Collective Belief; 4.8 Exit Champion; 4.9 When to Give Up; 4.10 Prologue to the Denver International Airport Case Study; 4.11 Denver International Airport; Background; Airports and Airline Deregulation; Does Denver Need a New Airport?; Enplaned Passenger Market; Land Selection; Front Range Airport; Airport Design; Project Management; Baggage-Handling System; Early Risk Analysis; March 1991; April 1991; May 1991; August 1991; November 1991.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Project management; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Project management; Project management; Electronic books; Electronic books